(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: The persistence of symptoms after Covid-19 infection is a new area of interest for researchers. Objective: To determine the frequency of persistence of rheumatic symptoms after Covid-19 infection. Methods: This cross-sectional study was conducted at Combined Military Hospital (CMH), Dhaka from December 2021 to June 2022. A total of 173 patients who suffered from Covid-19 at least 6 months prior were enrolled. Data were collected using a pre-designed questionnaire over the phone regarding the persistence of symptoms and new rheumatic symptoms after Covid-19 infection. Results: A total of 173 patients were enrolled; the average age was 43.5±18.2 years and 66% were male. Almost half of the study participants (44.5%) were serving military personnel and 87.9% of them were vaccinated against Covid-19. Among the study participants, 28.9% required supplemental oxygen to treat Covid-19. After Covid-19 suffering, 28.9% had persistent symptoms and 9.8% had persistent musculoskeletal symptoms. After Covid-19, 6(3.47%) developed new joint symptoms; of them, one was diagnosed with Rheumatoid Arthritis (RA), one with Osteoarthritis (OA) and 4 remained undifferentiated. Though the persistence of symptoms was numerically less in military personnel, it was not statistically significant (p 0.076). Conclusion: Covid-19 infection may trigger the development of inflammatory arthritis. Further studies are needed to assess the molecular pathophysiological changes and to confirm causal relationship. JAFMC Bangladesh, Vol 21, No 2 (December) 2025:14-16